Blackcurrant (Ribes nigrum) lowers sugar-induced postprandial glycaemia independently and in a product with fermented quinoa: a randomised crossover trial - Lappi, Jenni; Raninen, Kaisa; Väkeväinen, Kati; Kårlund, Anna; Törrönen, Riitta; Kolehmainen, Marjukka (British journal of nutrition, 2021)
Berries rich in anthocyanins have beneficial effects on postprandial glycaemia. We investigated whether blackcurrant (75 g in a portion) independently and in a product with fermented quinoa induced similar effects on the sugar-induced postprandial glucose metabolism as observed before with 150 g of blackcurrant. Twenty-six healthy subjects (twenty-two females and four males) consumed four test products after fasting overnight in a randomised, controlled crossover design. Each test product portion contained 31 g of available carbohydrates and had similar composition of sugar components: 300 ml water with sucrose, glucose and fructose (SW; reference), blackcurrant purée with added sugars (BC), a product consisting of the blackcurrant purée and a product base with fermented quinoa (BCP) and the product base without blackcurrant (PB). Blood samples were collected at 0, 15, 30, 45, 60, 90, 120 and 180 min after eating each test product to analyse the concentrations of glucose, insulin and NEFA. In comparison with the SW, the intake of both the BC and BCP resulted in reduced glucose and insulin concentrations during the first 30 min, a more balanced decline during the first hour and improved glycaemic profile. The BCP induced more efficient effects than the BC due to the product base with fermented quinoa. A rebound of NEFA after the sugar-induced hypoglycaemic response was attenuated at the late postprandial phase by the BC and BCP. In conclusion, we showed that 75 g of blackcurrant and the product with fermented quinoa were able to lower postprandial glycaemia and insulinaemia.